DÓRETIWShILIK MEKTEPLERIN XALÍQARALÍQ AKKREDITACIYADAN ÓTKERIWDIŃ ÁHMIYETI - Kazimbetova, Z.M. (SCIENCE and SOCIETY, 2026)
In this article, the organization provides information about the creation of the international company Cognia, Inc., this article covers the main areas of work and the accreditation process for educational institutions. A scientific analysis of the organization’s activities and the results of research on this topic is provided. Cognia’s accreditation process is explained by using examples from creative schools.